Perbandingan Variasi Media Alternatif dengan Berbagai Sumber Karbohidrat Terhadap Pertumbuhan Candida albicans - Nurdin, Erpi; Nurdin, Gaby Maulida (bionature, 2020)
Abstract. In the growth of microorganisms such as fungi, it is necessary to grow a medium that can provide nutrients and as an energy source. Other alternative carbohydrate sources include potatoes, breadfruit, sago, and cassava, which is a distinctive and easy to find food companion. This type of research is descriptive with cross sectional design that aims to determine the difference in alternative media variation from various sources of carbohydrate to Candida albicans. The samples were then made to be the treatment for the creation of alternative media from various carbohydrate sources that further carried out the growth test against Candida albicans. The results of the study are the average growth of colonies on alternative media from Potato carbide sources, namely 655 colonies, breadfruit 1380 colonies, cassava 862 colonies, 372 sago colonies, and semi-synthetic media as a control of 874 colonies. This indicates there is growth of Candida albicans on all alternative media so that it can be used as an alternative medium of fungi growth, as well as the best growth of Candida albicans found in the media Breadfruit Dextrose Agar. Keywords: alternative media, carbohydrate sources, Candida albicans